PENGARUH UKURAN PERUSAHAAN, RASIO LANCAR, FINANCIAL LEVERAGE DAN LABA SEBELUM PAJAK TERHADAP PEMILIHAN METODE AKUNTANSI PERSEDIAAN (Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2015) - Nanda Setya Agustin, 13.05.52.0158; Susilowati, Yeye (Students' Journal of Accounting and Banking, 2017)
This study examined the effect of firm size, the current ratio, financial leverage and profit before tax to the selection method of inventory accounting. This research was conducted at the Indonesian Stock Exchange by using analysis unit manufacturing company. The dependent variable is declared with the dummy variable is the number 0 for companies using the FIFO method and the numbers 1 to companies using the average method. The sampling method using purposive sampling the study period of 2013 to 2015, obtained 192 companies that qualify as research samples. And the relationship between variables or effect described by using logistic regression analysis using SPSS version 19. The results show that the variable size of the company and the current ratio not significant but variable financial leverage and profit before tax significantly influence the selection method of inventory accounting.Keywords: Company Size, Current Ratio, Financial Leverage, Profit Before Tax and Inventory Accounting Methods